2005
DOI: 10.1111/j.1442-2050.2005.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of esophageal myotomy and myectomy on the lower esophageal sphincter pressure profile: intraoperative computerized manometry study

Abstract: The surgical treatment of achalasia, based on Heller's myotomy is the procedure of choice to reduce the sphincterial high pressure zone, either by laparotomy or, most recently, by laparoscopy. What is the right length of the myotomy? Many authors have reported 10-15% postoperative residual dysphagia, due to the incomplete gastric myotomy and not to esophageal pouring. The aim of this study is to experimentally determine the modifications induced by Heller's myotomy and myectomy of the esophago-gastric junction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…However, there is surprisingly little research about how far to carry the myotomy past the GEJ to the stomach (or up the esophagus for that matter). Di Martino et al [16] have shown in an animal model the need for extending the myotomy 2 to 3 cm on to the stomach. In their study, this gastric extension was much more effective in ablating the LES than was the esophageal portion of the myotomy.…”
Section: Discussionmentioning
confidence: 98%
“…However, there is surprisingly little research about how far to carry the myotomy past the GEJ to the stomach (or up the esophagus for that matter). Di Martino et al [16] have shown in an animal model the need for extending the myotomy 2 to 3 cm on to the stomach. In their study, this gastric extension was much more effective in ablating the LES than was the esophageal portion of the myotomy.…”
Section: Discussionmentioning
confidence: 98%
“…The issue of a limited myotomy has been studied clinically. 11,12 However, this technique encompasses division of the longitudinal and the circular muscular bundles. Our study showed that a selective (circular bundles) and short myotomy may achieve a good functional outcome.…”
Section: Resultsmentioning
confidence: 99%
“…A number of authors have reported a gastric extension of the myotomy from 1 to 4 cm [11,12,16]. Di Martino et al have reported that extending the myotomy 2-3 cm on to the stomach is more effective in ablating the LOS and to relieve dysphagia [17]. Oelschlager extended the myotomy 3 cm on the stomach wall [18].…”
Section: Discussionmentioning
confidence: 98%